A Study Mathematics Achievement by Using Problem-Based Learning for Grade 1 Students - PHOMMANITH , Khamsone; OUNKEO, Chalearnsack; BOUSITH , Oudom; KEOPHASITH, Vatsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this research, was to compare mathematics achievement by using problem-based learning management of grade 1 students. To compare the mathematical achievement by using problem-based learning management of Grade 1 students before and after learning activities and to study the attitudes toward mathematics after by using problem-based learning management of grade 1 students. The samples for this research consisted of 22 students at first semester in 2020-2021 grade 1 Class 1 from Kiettisack International School - KIS Luang Prabang, Luang Prabang District, Luang Prabang Province. using cluster random sampling. The research instruments included problem-based learning management plans, Mathematical achievement test and the measurement of the attitude toward mathematics. The data analyzed by mean, standard deviation and t-test. The findings found that: 1). Students have mathematical learning achievement by management problem-based learning above 75% with statistical significance at 0.5. 2). Students achieve mathematical learning outcomes by modeling learning arrangements. Use problem after school as higher as before school with statistical significance at the 0.05 level. 3). Students 'attitudes toward problem-based mathematics were organized as a whole at a multi-level level when it was found that the teachers' readiness to teach had the highest average, followed by the teacher's understanding and attentiveness of the students and teachers to make learning mathematics fun.